2019
DOI: 10.1126/sciadv.aax5088
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbes drive phylogenetic diversity-productivity relationships in a subtropical forest

Abstract: The relationship between plant diversity and productivity and the mechanisms underpinning that relationship remain poorly resolved in species-rich forests. We combined extensive field observations and experimental manipulations in a subtropical forest to test how species richness (SR) and phylogenetic diversity (PD) interact with putative root-associated pathogens and how these interactions mediate diversity-productivity relationships. We show that (i) both SR and PD were positively correlated with biomass for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 45 publications
2
46
1
1
Order By: Relevance
“…In addition to these biotrophic fungal guilds, the dissimilarities among free-living soil fungal communities significantly increase over large spatial scales and with increasing plant phylogenetic distance, however, the explained variation is relatively lower than that of pathogens and EcM fungi (Yang et al, 2019). Controlled experiments also suggest that soil microorganisms that are obligately symbiotic with some trees usually promote growth on these trees or closely related species, but do not affect growth as much on distantly related species (Liang et al, 2019). These results suggest that closely related hosts usually have certain fungal specificities.…”
Section: Phylogenetic Signals In Orchid-omf Interactionsmentioning
confidence: 99%
“…In addition to these biotrophic fungal guilds, the dissimilarities among free-living soil fungal communities significantly increase over large spatial scales and with increasing plant phylogenetic distance, however, the explained variation is relatively lower than that of pathogens and EcM fungi (Yang et al, 2019). Controlled experiments also suggest that soil microorganisms that are obligately symbiotic with some trees usually promote growth on these trees or closely related species, but do not affect growth as much on distantly related species (Liang et al, 2019). These results suggest that closely related hosts usually have certain fungal specificities.…”
Section: Phylogenetic Signals In Orchid-omf Interactionsmentioning
confidence: 99%
“…The positive relationship between plant diversity and productivity has been found in natural and experimental communities and is now widely accepted (Huang et al., 2018; Liang et al., 2019; Zak et al., 2003). Several studies have shown that diversity of primary producers also can enhance the diversity of associated trophic levels (Fornoff et al., 2019; Lefcheck et al., 2015; Scherber et al., 2010; Schuldt et al., 2019).…”
Section: Introductionmentioning
confidence: 97%
“…According to the disease–diversity hypothesis, a high species diversity confers disease resistance through dilution of host density (Burdon, 2001; Mitchell et al., 2003), which is also referred to as dilution effects (Keesing et al., 2006). This might be explained by a reduced average susceptibility of individuals in a more diverse plant community (Liang et al., 2019; Shurtleff & Averre III, 1997). Moreover, a reduced host abundance and an increased host spatial distance might reduce the pathogen transmission, reducing the pathogen impact in more diverse plant communities as predicted by the encounter reduction mechanism (Johnson et al., 2015; Keesing et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, soil biodiversity loss did not affect plant diversity-productivity relationships in diverse plant communities. Past research shows soil pathogen suppression has more beneficial effects, while the absence of soil mutualists exerts stronger detrimental effects on biomass production in less diverse plant communities, and consequently, influences plant diversity-productivity relationships (Klironomos et al 2000;Maron et al 2011;Schnitzeret al 2011;Luo et al 2017;Liang et al 2019;Wang et al 2019a). However, soil biodiversity loss did not alter the strength of plant diversity effects on plant biomass production in the present study.…”
Section: Discussionmentioning
confidence: 99%